Decline of Ves v 5‐specific blocking capacity in wasp venom‐allergic patients after stopping allergen immunotherapy. Issue 6 (28th March 2015) - Möbs, C.; Müller, J.; Rudzio, A.; Pickert, J.; Blank, S.; Jakob, T.; Spillner, E.; Pfützner, W.
Abstract: While allergen‐specific immunotherapy (AIT) is very efficient in hymenoptera venom (HV)‐allergic patients, long‐term outcome after finishing AIT is not well investigated, especially regarding mechanisms that are suggested to contribute to allergen‐specific tolerance. Here, we analyse the Ves v 5‐inhibitory activity of sera from wasp venom‐allergic patients using the novel cell‐free enzyme‐linked immunosorbent facilitated antigen binding (ELIFAB) assay. Compared to pre‐AIT, sera from patients undergoing AIT displayed an increased ability to inhibit Ves v 5 binding by IgE antibodies. In contrast, this inhibitory activity was reduced in patients having finished AIT 5–12 years ago. Allergen‐blocking capacity correlated with serum concentrations of Ves v 5‐specific IgG4 which rose during AIT but almost reached pretreatment levels in patients who had stopped AIT more than 5 years ago. These data raise questions about how long allergen tolerance is maintained in AIT‐treated HV‐allergic patients and suggest that the ELIFAB assay might be an easy‐to‐use tool assessing long‐term tolerance in patients treated with HV‐AIT.